Challenges and facilitators in the collection and treatment of aquatic biomass waste for the production of high-value products - Knudby, Torben; Eriksen, M. Lynn; Kjærsgaard, Niels C.; Hedegaard, Michael; Lund, Victor; Salvador, Rodrigo (European Journal of Sustainable Development, 2025)
The objective of this paper is to present challenges and propose solutions for the collection and treatment of aquatic biomass waste, specifically beach wreck, such as seagrass and seaweed, in the promotion of a circular bioeconomy. This paper explores various methodologies for the collection and treatment of beach wrack to optimize the recovery of valuable compounds contained within these biomass wastes. In order to do so, we identify and assess the efficacy of different collection techniques, including manual collection and mechanical raking, across diverse coastal environments and subsequently, the requirements of the state of biomass in post-collection treatment processes, such as cleaning, drying and quality tests are mapped to analyze the need to enhance the yield and quality of the recovered materials. Utilizing beach wreck as an alternative to virgin feedstock contributes significantly to advancing a circular bioeconomy, and the effectiveness and efficiency of collection techniques are crucial for making waste biomass suitable for the value recovery of the components contained in it. Keywords: aquatic biomass waste, beach wreck collection, waste valorization, circular bioeconomy, sustainable waste management.